Pengaruh Pengembangan Sumber Daya Manusia dan Kompetensi terhadap Kinerja Guru di Perguruan Al-Washliyah Amplas - Widiyantika, Widiyantika; Syafrizal, Syafrizal; Wibowo, Muhammad Prasetyo (JRMB (Jurnal Riset Manajemen & Bisnis), 2024)
The purpose of this study was to determine and analyze the effect of human resource development on teacher performance at Al-Washliyah Amplas college, to determine and analyze the effect of competence on teacher performance at Al-Washliyah Amplas college, to determine and analyze the effect of human resource development and competence on teacher performance at Al-Washliyah Amplas college. The population in this study were all teachers who worked at the Al-Washliyah Amplas college, totaling 38 teachers and the sampling was done by total sampling so that 38 respondents were sampled. Based on the results of the study it is known that there is a significant influence between human resource development and competence on teacher performance, there is a positive influence of human resource development variables and competence on teacher performance. Human resource development and competence on teacher performance together (multiple) there is positive and significant influence on Teacher performance